RESULTS OF PULMONARY METASTASES RESECTION WITH THE ND: YAG LASER AND ELECTROCAUTERY - Yu. A. Ragulin; E. I. Smolenov; V. S. Usachev (Исследования и практика в медицине, 2018)
Purpose. To assess the effectiveness of various techniques of surgery of pulmonary metastases based on the outcomes of surgery interventions, frequency of postoperative complications and overall survival of patients.Patients and methods. Ninety-seven patients with suspected lung metastases of known primary malignancies (47 men and 50 women, mean age of 46,5 years) were retrospectively included in two study groups between 1 January 2004 and 1 January 2016 and underwent pulmonary surgery with the Nd: YAG laser of the 1318 nm wavelength (Group A, n = 44) or with the electrocautery (Group B, n = 53).Results. A total of 151 operations were performed: 75 in Group A, 76 in Group B. The mean number of resected pulmonary lesions was 8,2 (95% CI: 5,2–11,1) in group A and 4,9 (95% CI: 3,7–6,0, p = 0,047) in group B. Additionally 87 lesions were evaporated due to small sizes (1–2 mm) in Group A. The mean time of surgery was 146 minutes in Group A and 113 minutes in Group B (p < 0,01).Post-surgery complications were diagnosed after 9 and 19 of interventions in Groups A and B, respectively. The most common complications were pneumonia, pneumothorax and subcutaneous emphysema. The number of Grade III complications according to Clavien-Dindo classification was 2 and3 inGroups A and B, respectively. The survival rates were computed for all patients: the one-year, three-year and five-year survival rates were 83,7%, 49,7% and 36,7%, respectively.Conclusion. The Nd:YAG laser with wavelength of 1318 nm allow extensive parenchymal resections without an increase in post-surgery complications and may have advantages in pulmonary metastasectomy, especially in patients with multiple pulmonary lesions.